THE REALISATION OF MEDIA FREEDOM AS A TOOL TO COMBAT CORRUPTION IN ZIMBABWE: LESSONS FROM SOUTH AFRICA - Windell Nortje, Windell; Chikodza, Englebert (Journal of Anti-Corruption Law, 2024)
Corruption is rife in South Africa and Zimbabwe. The media plays an important role in exposing corruption. In South Africa, the media exposed a multi-billion-dollar corruption saga in 2016 involving the former president and his business associates which the media dubbed “state capture”. Most of the state-owned entities were captured and served as vehicles for grand corruption. Today, South Africa has yet to recover from the saga exposed in 2016. In fact, the incumbent South African president, Cyril Ramaphosa, has also been under investigation for money laundering and corruption while simultaneously reaffirming his ruling party’s fight against corruption. The media continues to keep the executive on its toes and should be praised for their efforts. South Africa’s neighbour, Zimbabwe, has a different outlook. While corruption in Zimbabwe is even worse than in South Africa, the media does not have the similar freedom to expose corruption. There exists a constant fear of retaliation for blowing the whistle on corrupt activities. It is common for journalists to be detained for speaking out. Media laws should be adopted to affirm media freedom. Instead they have often been adopted, especially in Zimbabwe, to demonise the media. This paper essentially analyses the importance of the media in exposing corruption in Zimbabwe and how their role can be protected and enhanced. This paper makes an important contribution towards the protection of media freedom in light of strengthening anti-corruption efforts in South Africa and Zimbabwe. It is one of the first studies to examine the achievements and shortcomings of media freedom in relation to corruption in South Africa and Zimbabwe. The article will commence by examining conceptual aspects regarding corruption and the role of the media. It will then examine the regulatory framework governing the rights of media in both jurisdictions. What follows next is an analysis of several case studies amplifying the problems faced by the media in Zimbabwe. This is followed by analysing the lessons Zimbabwe can learn from South Africa’s approach to media freedom. The article will conclude by providing several recommendations.